Acute Effects of White Button and Shiitake Mushroom Powder Supplementation on Postprandial Lipemia and Glycemia Following a High-Fat Meal - Lillian, A. Talal; Huipei, Wang; Brian, T. Williams; Matthew, J. Morris; Peter, J. Horvath (International Journal of Nutrition, 2023)
Background To determine the acute effects on postprandial lipemia and glycemia by supplementing a high-fat meal with either white button (WB) or shiitake (SH) mushroom powder. Methods Nine healthy participants (4-male, 5-female, 23.3±1.3 years, 17.8±6% body fat, 56.2±11.4kg fat free mass) consumed a control hamburger. At one-week intervals, after consumption of a control meal, participants consumed hamburgers in random order, supplemented with 14g of either WB or SH mushroom powder. Peripheral blood for lipids (triglycerides, high-density lipoprotein HDL, low-density lipoprotein LDL), and glucose was obtained at baseline (t=0 hours) and postprandially every two hours for six hours. Data were analyzed using linear mixed effects models. Results Lower LDL levels were observed for both SH and WB burgers compared to the control burger (p=0.0007) over the six-hour period. Mushroom powder content did not alter triglyceride, HDL, or glucose levels. Gender affected triglyceride and HDL levels over the treatment course. Triglyceride levels were higher in males (p=0.0084), and HDL levels were lower in females (p=0.0005). Triglyceride and glucose levels were higher, (p< 0.001 and p< 0.0001 respectively), during the postprandial time course (t=0, 2, 4, 6 hours). Conclusions Supplementing SH or WB mushrooms during a high-fat meal may lower serum LDL levels.
Keywords: Mushroom supplementation; postprandial lipemia; postprandial glycemia; Shiitake mushrooms; White Button mushrooms; fatty acid/ lipid metabolism